Performance of broilers fed diets using an analog of Peruvian fish meal - Mateo, Carmencita D.; Centeno, Josephine R.; Billena, Mylen S. (2000)
Three hundred fifty (350) day-old male broiler chicks were used to evaluate the substitution of Peruvian fish meal (PFM) with a fish meal analog (FMA) in various proportions. Substituting FMA for PFM on an equal weight basis significantly (P < 0.05) increased body weight gain and improved feed efficiency of chicks during their first 21 days of life. Chicks fed 100% PFM (control) compensated for their slower weight gain and lower feed efficiency during the growing period. This resulted in similar chick performance among all dietary treatments during the entire duration of the trial. The economic evaluation of the different diets shows that the FMA can be a substitute for PFM without reduction in performance.
Keywords: Broilers (Poultry) -- Feeding and feeds; Broiler chickens -- Feeding and feeds